Design of a User-Friendly Financial Tracker for Daily Household Spending Based on JavaScript and Bootstrap - Dina Ramadhania; Muhammad Romadhona Kusuma (Journal of Innovation and Computer Science, 2025)
In today's digital era, recording expenses is crucial to effective financial management, especially for individuals and Micro, Small, and Medium Enterprises (MSMEs). This study aims to design and implement a web-based financial system using JavaScript and Bootstrap 5 that can record transactions dynamically and in real time. The system is designed to be lightweight, responsive, and easy to use. Thus, it is accessible to users with varying levels of technological literacy. Evaluation results find that the system records expenses accurately and receives positive feedback from users regarding its usability. In particular the system is especially suitable for household users, particularly individuals who manage their daily spending routines at home.